Hybrid teaching in the school context: Challenges and possibilities for implementation in basic education (Research, Society and Development, 2023)
Blended Learning emerged to leverage student learning by adding the power of being the protagonist of the learning process and expanding greater engagement and efficiency. This modality has been widely used as a methodological proposal for teaching education in times of a pandemic, after the first days of social isolation have passed. Thus, this article aims to analyze the degree of student satisfaction in relation to the hybrid methodology in a Basic Education School of the Public Education Network, in addition to investigating the process of implementing this methodology by observing the adaptation of students through a case study. As a research tool, a questionnaire containing closed and open questions was applied with the intention of verifying the students' satisfaction in relation to the hybrid teaching method, aiming to observe the negative and positive points from the perspective of the students who participate in this process. Based on the analysis of the data found, it is concluded that the implementation of the hybrid teaching model is satisfactory, in the perception of the students. However, because it is a new teaching model in the context of Basic Education, some students have not yet got used to the routine and have difficulties in dealing with the method.